1972
DOI: 10.1136/pgmj.48.565.678
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculomas of the brain in Britain

Abstract: Summary Reports of three patients with tuberculomas of the brain are presented. The mode of presentation and clinical features of this condition are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…In 1933 a survey of postmortem records (Garland and Armitage, 1933) revealed that 3400 of all cerebral tumours were tuberculomas. By 1940 an analysis of 2,190 brain tumours collected from recent reviews (Wilson, 1940) showed that only 3 6'/ were tuberculomas and a more recent review (Maurice-Williams, 1972) demonstrated an incidence of 0-15%0 among 2,200 intracranial tumours seen at the Guy's-Maudsley neurosurgical unit from 1951-1972. In 1970 Kocen and Parsons (1970) drew attention to some unusual neurological complications of tuberculosis, particularly in non-European immigrants, though none of their patients had intracranial tuberculomas. We wish to report three patients with verified intracranial tuberculomas who have presented to this unit in the past 12 months.…”
mentioning
confidence: 99%
“…In 1933 a survey of postmortem records (Garland and Armitage, 1933) revealed that 3400 of all cerebral tumours were tuberculomas. By 1940 an analysis of 2,190 brain tumours collected from recent reviews (Wilson, 1940) showed that only 3 6'/ were tuberculomas and a more recent review (Maurice-Williams, 1972) demonstrated an incidence of 0-15%0 among 2,200 intracranial tumours seen at the Guy's-Maudsley neurosurgical unit from 1951-1972. In 1970 Kocen and Parsons (1970) drew attention to some unusual neurological complications of tuberculosis, particularly in non-European immigrants, though none of their patients had intracranial tuberculomas. We wish to report three patients with verified intracranial tuberculomas who have presented to this unit in the past 12 months.…”
mentioning
confidence: 99%
“… 1 The majority of our understanding of the disease process comes from reports such as these, since during the same period one Western author noted only three cases at a British neurosurgical service that had treated 2200 intracranial tumors. 9 Since that era there have been decreasing numbers of reports, as a PubMed search revealed only five non-overlapping large case series with at least 50 patients in the contemporary English medical literature, i.e ., the last five decades. 1 , 2 , 10 , 11 …”
Section: Discussionmentioning
confidence: 99%
“…Mycobacteria other than the tubercle bacillus, which are responsible for 0·15% to 4·0% of intracranial tumours in western countries (Kummer et al ., 1981; Maurice‐Williams, 1972), represent a novel agent of pituitary granuloma. These bacteria are usually nonpathogenic for humans, but occasionally cause progressive and potentially destructive diseases.…”
Section: Discussionmentioning
confidence: 99%